1923 Cal. Stat. 696, § 2 - (:unkn) unknown (My University, 1923)
Prohibited ownership, possession, or control of any pistol, revolver or concealable firearm by any noncitizen or felony convicts.
Keywords: POSSESSION - DANGEROUS PERSONS